Pregnancy and Preterm Birth: A Systematic Review of Risk Factors and Prevention - Rajia, Rajia (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This systematic literature review examines the multifaceted risk factors contributing to preterm birth and evaluates the effectiveness of various prevention strategies. By synthesizing existing research, the study aims to provide a comprehensive understanding of the biological, behavioral, and socioeconomic determinants of preterm birth and identify gaps for future research. Research Design and Methodology: A qualitative approach was utilized to systematically search electronic databases to gather relevant peer-reviewed articles, systematic reviews, and meta-analyses published between 2000 and 2024. The study employed thematic analysis to identify key themes related to preterm birth risk factors and prevention strategies, incorporating approximately 150 high-quality studies into the synthesis. Findings and Discussion: The review identified critical biological factors such as maternal age and genetic predispositions, with younger and older mothers facing increased risks due to complications like cervical insufficiency and chronic conditions. Inflammatory pathways, hormonal regulation, and uteroplacental blood flow emerged as significant mechanisms leading to preterm labor. Behavioral factors, including smoking and substance abuse, along with poor nutritional status, exacerbated the risk. The discussion highlights the necessity for integrative prevention strategies that address these diverse factors through medical, behavioral, and socio-economic interventions. Implications: The findings highlight the importance of personalized medical care, comprehensive public health strategies, and targeted policy initiatives in reducing preterm birth rates. Future research should focus on developing integrative models of care and customized prevention approaches, taking into account the complex interplay of identified risk factors.